PENGARUH MODEL PEMBELAJARAN INQUIRY TRAINING TERHADAP HASIL BELAJAR SISWA DI KELAS X SEMESTER II SMA NEGERI 1 PERCUT SEI TUAN T.P. 2013/2014 - Derlina .; Tonggol Barumun Hasibuan (UNIVERSITAS NEGERI MEDAN, 2014)
ABSTRACT The purpose of research is to determine the effect of student learning outcomes with inquiry learning model to determine the training and learning activities of students during the learning process in the subject matter and the temperature of the heat in the second half of class X SMA Negeri 1 Percut Sei Tuan. This research is a quasi experiment. The population is the entire second semester of tenth grade students of SMA Negeri 1 Percut Sei Tuan consisting of 4 classes. Sampling was done by cluster random sampling MIA3 elected as class class X and class X experiments MIA2 as the control class. The instruments used in the form of multiple-choice tests and observation sheets. Results were obtained an average value 38.86 pretest experimental class and control class pretest 37.57. The average value of 76.29 posttest experimental class and control class 62.86. Increased activity of the experimental class students overall increase was 33% category. Based on the analysis of the hypothesis testing, the results of student learning as a result of the influence of the inquiry learning model of training is better than conventional learning on material temperature and heat. Keywords: learning model of inquiry training, learning results ABSTRAK Tujuan Penelitian untuk mengetahui pengaruh hasil belajar siswa dengan model pembelajaran inquiry training dan untuk mengetahui aktivitas belajar siswa selama proses pembelajaran pada materi pokok suhu dan kalor di kelas X semester II SMA Negeri 1 Percut Sei Tuan. Jenis penelitian ini adalah quasi eksperiment. Populasi dalam penelitian adalah seluruh siswa kelas X semester II SMA Negeri 1 Percut Sei Tuan yang terdiri dari 4 kelas. Pengambilan sampel dilakukan dengan cara cluster random sampling terpilih kelas X MIA3 sebagai kelas eksperimen dan kelas X MIA2 sebagai kelas kontrol. Instrumen yang digunakan dalam bentuk tes pilihan berganda dan lembar observasi. Hasil penelitian diperoleh nilai rata-rata pretes kelas eksperimen 38,86 dan pretes kelas kontrol 37,57. Nilai rata-rata postes kelas eksperimen 76,29 dan kelas kontrol 62,86. Peningkatan aktivitas siswa kelas eksperimen secara keseluruhan 33% kategori peningkatan sedang. Berdasarkan hasil analisis uji hipotesis satu pihak, diperoleh hasil belajar siswa akibat pengaruh model pembelajaran inquiry training lebih baik daripada pembelajaran konvensional pada materi suhu dan kalor. Kata kunci : model pembelajaran inquiry training, hasil belajar